The role of a playwright in the development of theater audience - Dragin Dušica (Zbornik Radova Akademije Umetnosti, 2020)
The purpose of this paper is to point out an innovative approach in the development of young theater audience. The starting point was a disinterest of young people to be actively involved in culture and their dissatisfaction with the offer of cultural content in the cities where they live, so the subject of research is defined as a search for a theory that will serve as a basis for finding appropriate solutions (models) for the development of young theater audience. The first part of the paper deals with the audience, its development and importance for cultural management. The second part analyses the notion of motive, as the dominant characteristics of interest, with a focus on the theory of functional autonomy of motives by Gordon Allport and its possible implementation in the process of motivating young people to go to theater. Functional autonomy considers drives as diverse, independent, contemporary systems that grow out of previous systems but are functionally independent of them. Some 'instrumental' activities, i.e. forms of behavior that served to satisfy a primary motive, over time can turn into goals and become drives. The assumption is that it is theoretically possible to interest young people in theater if theatrical performances would address topics or issues close to them. This assumption is confirmed by results of a research that speak in favor of the fact that a large percentage of Novi Sad high school students, who rarely or never go to theater, would be motivated to watch such an "instrumental theater". It has been observed that playwrights are to have a leading role in this process. Instead of a conclusion, there are presented effective recommendations for creating such performances for young people.